Viral vector vaccines - McCann, N; O'Connor, D; Lambe, T; Pollard, AJ (Elseveir, 2022)
Over the past two years, the SARS-CoV-2 pandemic has highlighted the impact that emerging pathogens can have on global health. The development of new and effective vaccine technologies is vital in the fight against such threats. Viral vectors are a relatively new vaccine platform that relies on recombinant viruses to deliver selected immunogens into the host. In response to the SARS-CoV-2 pandemic, the development and subsequent rollout of adenoviral vector vaccines has shown the utility, impact, scalability and efficacy of this platform. Shown to elicit strong cellular and humoral immune responses in diverse populations, these vaccine vectors will be an important approach against infectious diseases in the future.